Modelling hydrate deposition and sloughing in gas-dominant pipelines. (February 2018) - Di Lorenzo, Mauricio; Aman, Zachary M.; Kozielski, Karen; Norris, Bruce W.E.; Johns, Michael L.; May, Eric F.
Graphical abstract: Highlights: A newly developed model for hydrate blockages in gas-dominated pipelines is presented. The model is validated against an extensive set of flowloop data. The growth rate and effective shear strength of the hydrate deposit are estimated. Our first estimations of the effective shear strength are in the range of 100–200 Pa. At same subcooling MEG increased deposit growth rate, but shear strength decreased. Abstract: We present a model for hydrate deposition and sloughing in gas dominated pipelines which allows for rapid estimations of the pressure and temperature profiles along a horizontal pipeline during normal operation in the hydrate forming region in the presence of monoethylene glycol (MEG). Previous models assume that the hydrate deposit growing at the pipe wall is stable, which may lead to an overestimation of the pressure drop over time. Hydrate growth rates were calculated using a classical hydrate kinetic model combined with a simplified two-phase flow model for pipelines in the annular flow regime with droplet entrainment. Hydrate growth at the pipe wall, deposition of hydrate particles from the gas stream and sloughing due to shear fracture of the deposited film contributed to the evolution of the hydrate deposit. The model parameters included a scaling factor to the kinetic rate of hydrate growth and a particle deposition efficiency factor. The fraction of deposited particles forming a stable hydrate film at the pipe wall through sintering and the shear strength of the deposit were introduced as two additional parameters to enable simulation of sloughing events. The tuned model predicted hydrate formation within 40% and pressure drop within 50% of measurements previously obtained in a gas-dominated flow loop over a wide range of subcoolings, MEG concentrations and high and intermediate gas velocities. The observed decrease of the kinetic factor with decreasing gas velocity indicated larger resistances to hydrate growth in the entrained droplets at lower flow rates, while the increase of the deposition parameter with MEG concentration was consistent with a particle adhesion/cohesion mechanism based on the formation of a capillary bridge. The preliminary sloughing model presented in this work, combined with flowloop testing, has allowed the first in-situ determinations of the effective shear strength of the hydrate deposits (in the range of 100–200 Pa) which is a key property to predict hydrate detachment and accumulation in gas-dominated pipelines.